Low-risk gestational trophoblastic neoplasia outcome after treatment with VMP regimen from 2005 to 2017 - Chen-Chen Zhu; Han-Yuan Liu; Ying Wei; Zhen Shen; Li-Li Qian; Wei-Guo Song; Juan Wang; Da-Bao Wu; Xue-Fen Zhang; Ying Zhou (Elsevier, 2019)
Objective: To evaluate the efficacy and toxicity of VMP regimen applied to the patients with low-risk gestational trophoblastic neoplasia (LR-GTN) treated in Anhui provincial hospital. Materials and methods: Between 2005 and 2017, 87 patients with low-risk gestational trophoblastic neoplasia received VMP regimen, consisted of vincristine (VCR), methotrexate (MTX) and platinum (cisplatin, carboplatin or nedaplatin), 68 of whom received VMP as their first-line chemotherapy, and 19 methotrexate-failed patients received VMP regimen as their second-line chemotherapy. The staging and scoring system was based on International Federation of Gynecology and Obstetrics (FIGO 2000) criteria. We describe and analyze their baseline characteristics, remission/resistance/recurrence rates, adverse reactions and prognosis. Results: The first-line VMP protocol can achieve an 83.8% remission rate and it tended to develop resistance when the pretreatment β-hCG reaches 7503.5 IU/L, and can achieve complete remission with FAV and EMA-CO as the salvage regimen. Among the 19 methotrexate-failed patients, 2 of whom were yet resistant to VMP regimen, followed by several courses of salvage chemotherapy such as FAV and EMP, and achieved 89.5% remission rate in second-line VMP group. Resistance to this regimen was obviously related with higher pre-treatment HCG whether used as primary or salvage treatment. Severe myelosuppression (grade 3 or 4) was shown in 4 (5.9%) of 68 cases, of which none was grade 4. Conclusion: For patients diagnosed with LR-GTN VMP regimen was a safe and effective treatment with a high rate of remission. Keywords: Low-risk gestational trophoblastic neoplasia, Vincristine, Methotrexate, Platinum, Efficacy